PENGGUNAAN LARUTAN FERMENTASI KULIT SINGKONG DAN CUKA TERHADAP MASA SIMPAN FILET NILA MERAH BERDASARKAN JUMLAH MIKROBA PADA PENYIMPANAN SUHU RENDAH - Maharani, Annisa Nur; Liviawaty , Evi; Yustiati, Ayi; Pratama, Rusky Intan (Jurnal Perikanan Unram, 2025)
Tilapia filet is a fishery product that is widely favored because of its high protein content and ease of processing. However, this product has a relatively short shelf life, so natural preservation efforts are needed to extend its shelf life. This study aims to determine the optimal concentration of vinegar in the fermentation process of cassava peels to extend the shelf life of red tilapia fillets based on the number of bacteria during low-temperature storage. This research was carried out at the Fisheries Product Processing Laboratory, Biotechnology Laboratory, Aquaculture Laboratory, Faculty of Fisheries and Marine Sciences, Padjadjaran University in February 2024. This study was carried out by soaking red tilapia fillets using a fermented solution of cassava peel with different vinegar concentrations, consisting of 5 treatments, namely 0%, 0.5%, 1%, 1.5%, 2% and stored at low temperatures (50-100 C). The parameters observed were the number of bacterial colonies, and the degree of acidity (pH). The concentration of 0% observation was carried out on the 1st, 3rd, 6th, 7th, 8th, 9th day while the concentration of 0.5%, 1%, 1.5%, 2% was observed on the 1st, 4th, 7th, 8th, 9th, 10th, 11th, 12th and 13th days. Based on the results of the research that has been conducted, it can be concluded that a fermented solution of cassava peel with a vinegar concentration of 1% is the best to prolong red tilapia fillets based on the number of microbes and pH. The addition of 1% cassava peel fermentation solution can maintain the freshness of the fish until the 12th day with a total number of microbes of 3.3 x 107 with a pH value of 6.70